Towards an eco-practical theology: An eschatological horizon of true hope - Dames, Gordon Ernest (HTS teologiese studies, 2024)
The ecological crisis in the world necessitates the reconfiguration of the hegemony of modern science, theology, politics, economics and technology – the root cause of a pending ecological catastrophe. The aim is to redress a growing culture of apathy in the context of devastating weather conditions, social and political discord, and unrelenting violent wars. Public theology serves as a conceptual framework with transversal rationality as an interlocutor between the different theological (systematic, ethics, pastoral care and eco-theology), religious and philosophical perspectives. The theological ontology of care is presented followed by the role of communities of critical prophetic discourse. The notion of earth as a community leads to the prospect of a new eco-theology. Finally, the pending ecological catastrophe is reconceptualised in and through Christian eschatology. This is an inter- and intra-disciplinary discussion on the disastrous consequences of modernity and anthropocentric behaviour in terms of the current environmental crisis. Various scholars offer valuable insights into what the problem is, who responsible is for the environmental crisis, and how Christian communities should forge an accountability of care for the earth and vulnerable human beings. The eschatological reality of God’s preferred future remains a constant of hopeful and sustainable life in the Anthropocene age. It is recommended that we change the way we exist by transforming modernity as developed and sustained through theology, socio-political, economic and technological ‘advances’.Contribution: This article focussed on the ecological crisis because of anthropocentrism and distorted theological, political and socio-economic paradigms to serve human interests despite the consequences for the earth. We need to reconfigure interdisciplinary and intradisciplinary scientific approaches to embrace earth as a key scientific interlocutor. The ecological crisis should be conceptualised within the reality of Christian eschatology – Jesus Christ is ultimately, the eschaton.